2014
DOI: 10.1073/pnas.1312993111
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin D2 is a GATA4 cofactor in cardiogenesis

Abstract: The G1 cyclins play a pivotal role in regulation of cell differentiation and proliferation. The mechanisms underlying their cellspecific roles are incompletely understood. Here, we show that a G1 cyclin, cyclin D2 (CycD2), enhances the activity of transcription factor GATA4, a key regulator of cardiomyocyte growth and differentiation. GATA4 recruits CycD2 to its target promoters, and their interaction results in synergistic activation of GATA-dependent transcription. This effect is specific to CycD2 because Cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 54 publications
1
32
0
Order By: Relevance
“…6). GATA4 and TBX5 interact physically to activate gene expression synergistically in the heart (2), and multiple Gata4 transcriptional targets have been identified in the heart (1,4,5,7,22,64). Recent studies have indicated that GATA4 and TBX5 are essential for each other's transcriptional fidelity in the control of cardiac gene regulatory networks in mouse and human models (65,66).…”
Section: In Control Gli1mentioning
confidence: 99%
“…6). GATA4 and TBX5 interact physically to activate gene expression synergistically in the heart (2), and multiple Gata4 transcriptional targets have been identified in the heart (1,4,5,7,22,64). Recent studies have indicated that GATA4 and TBX5 are essential for each other's transcriptional fidelity in the control of cardiac gene regulatory networks in mouse and human models (65,66).…”
Section: In Control Gli1mentioning
confidence: 99%
“…1). A recent work uncovered a role for cyclin D2 as a cardiogenic coactivator of GATA4 and suggests a paradigm for cell-specific effects of cyclin D proteins (Yamak et al, 2014).…”
Section: Cyclin Dmentioning
confidence: 99%
“…In Vitro Pulldown Assay-Production of the GST-TBX5a and MBP-NKX2.5 constructs (where MBP is maltose-binding protein) and the pulldown assays were done as described previously (24).…”
Section: Methodsmentioning
confidence: 99%